2011
DOI: 10.3354/dao02349
|View full text |Cite
|
Sign up to set email alerts
|

Bait and the susceptibility of American lobsters Homarus americanus to epizootic shell disease

Abstract: Shell disease (SD) has been observed in lobster populations for almost a hundred years, but recently, rates of an epizootic form of shell disease (ESD) have increased in the southern New England (USA) area. A large proportion of fish in the diet of American lobsters Homarus americanus has been linked to increased rates of SD. Therefore, the use of fish as lobster bait may be linked to increased ESD rates in lobsters. Lobsters from the western portion of Martha's Vineyard, MA (41°N, 71°W), were randomly divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…There may be several reasons for the differences between the FA tracers and the stable isotope analysis. Bethoney et al (2011) demonstrated that δ 15 N values in lobster tissue reflect their long-term diet, so the time-period of our study may not have been long enough. Another consideration is that there may have been an insufficient amount of waste consumed to establish an isotopic signal, as lobsters are slow and periodic feeders (Bordner & Conklin 1981).…”
Section: Discussionmentioning
confidence: 91%
“…There may be several reasons for the differences between the FA tracers and the stable isotope analysis. Bethoney et al (2011) demonstrated that δ 15 N values in lobster tissue reflect their long-term diet, so the time-period of our study may not have been long enough. Another consideration is that there may have been an insufficient amount of waste consumed to establish an isotopic signal, as lobsters are slow and periodic feeders (Bordner & Conklin 1981).…”
Section: Discussionmentioning
confidence: 91%
“…Thus, in our single experimental system, the source of the bacteria identified in association with DISD-induced shell pathology is likely either the herring used to prepare the diet or the bacterial community in the aquarium water taken in from Boston harbor; as such, extrapolations to bacterial communities of shell disease in wild lobsters are not easily made. It is notable however, that some of the same bacteria detected in DISD lesions here are also commonly detected in wild outbreaks of shell disease and wild lobsters are known to consume high levels of fish from baited traps (Bethoney et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…In laboratory experiments, lobsters fed a diet of herring alone experienced significantly more shell disease and more mortality than those fed a wild diet (Myers and Tlusty 2009), but this was likely not ESD, rather it was a diet-induced form of the classical shell disease. In a field study, the stable isotope ratios of nitrogen were assessed in wildcaught lobsters with varying degrees of ESD, and whereas the 15 N levels indicated lobsters were eating large amounts of fish in their diet, there was little association between high levels of 15 N and the disease (Bethoney et al 2011). Moreover, ESD does not occur in other areas where herring is used broadly as bait within lobster fisheries.…”
Section: Epizootic Shell Disease (Esd)mentioning
confidence: 99%